2017
DOI: 10.1136/bmjopen-2016-014847
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of economic evaluations of seasonal influenza vaccination for the elderly population in the European Union

Abstract: ObjectivesThe Council of the European Union (EU) has recommended that action should be taken to increase influenza vaccination in the elderly population. The aims were to systematically review and critically appraise economic evaluations for influenza vaccination in the elderly population in the EU.MethodsElectronic searches of the NHS Economic Evaluation, Health Technology Assessment, MEDLINE and Embase databases were run to identify full economic evaluations. Two levels of screening were used, with explicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 33 publications
(85 reference statements)
1
30
0
3
Order By: Relevance
“…The automatic search strategy was adapted from previous systematic reviews on aTIV 24,25 and those on economic evaluations of influenza vaccines 13,18 and is reported in Supplementary file 1. Medline via Ovid, Embase, Database of Abstracts of Reviews of Effects (DARE) and the NHS Economic Evaluation Database (EED) were the primary information sources.…”
Section: Search Strategymentioning
confidence: 99%
See 3 more Smart Citations
“…The automatic search strategy was adapted from previous systematic reviews on aTIV 24,25 and those on economic evaluations of influenza vaccines 13,18 and is reported in Supplementary file 1. Medline via Ovid, Embase, Database of Abstracts of Reviews of Effects (DARE) and the NHS Economic Evaluation Database (EED) were the primary information sources.…”
Section: Search Strategymentioning
confidence: 99%
“…12 It is now widely acknowledged that annual influenza vaccination is a good value for money; this has been demonstrated in several systematic reviews of economic studies. [13][14][15] It is particularly cost-effective/cost-saving in the elderly; 13 indeed, seniors are the main internationally recognized target group for annual immunization campaigns. 1,16 Systematic reviews of economic evaluations are becoming increasingly common.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of the cost-effectiveness and benefits from influenza vaccination is ample across the literature, but the focus has been on countries with strong seasonality and therefore distinct influenza seasons, which is usually countries in which winter occurs. For example, Shields et al 4 performed a systematic review of economic evaluations of seasonal influenza vaccination for the elderly population in the European Union and found that most studies showed that vaccination is cost-effective. Other analyses have assessed whether quadrivalent vaccines are costeffective.…”
Section: Introductionmentioning
confidence: 99%